The Effects of Rising Female Labor Supply on Male Wages - Juhn, Chinhui; Kim, Dae Il (Journal of Labor Economics, 1999)
This article examines whether increases in female labor supply contributed to rising wage inequality and declining real wages of less skilled males during the 1980s. While male wage declines are concentrated in the 1980s, female labor supply growth slowed in the 1980s relative to the 1970s. Women also increased the relative supply of skill in the economy in the 1980s. Using state‐level data we estimate cross‐substitution effects between men and women. Once we account for demand changes we find little evidence that women substitute for men or that they contributed to the rapid inequality growth in the 1980s.